Computer nicknames as a means of self-presentation among young people (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article discusses the concepts of «identity» and «selfpresentation». The problem of identity formation in adolescence is analyzed.The dependence of self-presentation on the state of identity is established.Listed are the features of communication on the Internet. Computernicknames are considered as a way of self-presentation on the Internet.The results of a study of self-presentation of young men using computernicknames are presented. Computer nicknames are systematized andanalyzed. The dependence of the choice of a computer nickname on thestate of identity in young people is established. The role of a computernickname in the formation of identity is determined.
Keywords: adolescence; identity; self-presentation; computer alias; moratorium; comunication